Effects of work overload and job stress on employee performance: categorical moderation from polychronicity and work environment - Rian Andriani; Disman Disman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The increasingly fierce competition in the world of work requires companies to work effectively and efficiently in order to survive and develop better. The right strategic steps are needed by the company in facing the competition. Companies must be able to manage resources in order to provide satisfactory services so that they can achieve the planned goals and objectives. Testing the moderation categorical model using path analysis based on OLS (Ordinary Least Square) regression and bootstrap method using SPSS version 25 and PROCESS version 3.5 statistical tools by Andrew F. Hayes the 76th model for the object of this research. The research sample was 235 health workers. The result of this research is that polychronicity and work environment effectively moderate the effect of work overload on employee performance through job stress. Work stress can be reduced by improving the quality of employees in the company and providing the best employees in the work environment.